An Update of Research Examining College Student Alcohol‐Related Consequences: New Perspectives and Implications for Interventions. (14th December 2012) - Mallett, Kimberly A.; Varvil‐Weld, Lindsey; Borsari, Brian; Read, Jennifer P.; Neighbors, Clayton; White, Helene R.
<x xml:space="preserve">Abstract</x> The objective of this review is to provide an update on existing research examining alcohol‐related consequences among college students with relevance for individual‐based interventions. While alcohol‐related consequences have been a focus of study for several decades, the literature has evolved into an increasingly nuanced understanding of individual and environmental circumstances that contribute to risk of experiencing consequences. A number of risk factors for experiencing alcohol‐related consequences have been identified, including belonging to specific student subgroups (e.g., Greek organizations) or drinking during high‐risk periods, such as spring break. In addition, the relationship between students' evaluations of both negative and positive consequences and their future drinking behavior has become a focus of research. The current review provides an overview of high‐risk student subpopulations, high‐risk windows and activities, and college students' subjective evaluations of alcohol‐related consequences. Future directions for research are discussed and include determining how students' orientations toward consequences change over time, identifying predictors of membership in high‐risk consequence subgroups and refining existing measures of consequences to address evolving research questions.